INTERNAL CONTROL SYSTEM OF THE STATE ISLAMIC UNIVERSITIES IN INDONESIA: STUDYING THE EFFECTIVENESS AND RISK MANAGEMENT - Azharsyah Ibrahim; Ana Fitria; Azimah Dianah (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2019)
This study intends to analyze the effectiveness of the implementation of the internal control system at the State Islamic Universities in Indonesia (PTKIN) including identifying its risk management. The empirical study was conducted at Ar-Raniry State Islamic University (UIN Ar-Raniry) Banda Aceh. Primary data was gathered through a survey that was distributed to 128 respondents within the university. Additional data were collected using semi-structured in-depth interviews with nine key personnel of the internal control unit of several Islamic universities in Indonesia. The result shows that UIN Ar-Raniry, based on eight elements of the control environment assessed, has sufficient internal control system with a score of 62.79. However, many steps need to undertake by the university’s management to be more effective and able to reduce risk management. A similar condition was also found in other PTKINs as identified during the interviews process with their key personnel. It also found that the internal control system was effective in identifying 69 risk sources that could potentially have a negative impact on the university performance, especially in terms of financial report reliability, asset security, effectiveness and efficiency of activities, and compliance with regulations. Based on the results, it is expected that the PTKIN should be more focus on internal control activities and linked them to the risk assessment which are regularly evaluated.==============================================================================================Sistem Pengendalian Internal pada Perguruan Tinggi Keagamaan Islam Negeri di Indonesia: Kajian terhadap Efektivitas Pelaksanaan dan Risiko Pengelolaan. Kajian ini bertujuan untuk menganalisis efektivitas pelaksanaan sistem pengendalian internal pada Perguruan Tinggi Keagamaan Islam Negeri di Indonesia (PTKIN) termasuk mengindentifikasi risiko pengelolaan yang muncul. Studi empiris dilakukan pada Universitas Islam Negeri Ar-Raniry (UIN Ar-Raniry) Banda Aceh. Data primer dikumpulkan melalui angket yang didistribusikan kepada 128 responden, yang terdiri dari para pejabat dalam UIN tersebut. Data tambahan dikumpulkan melalui wawancara mendalam secara semi-terstruktur dengan sembilan personil kunci dari Satuan Pengawasan Internal PTKIN BLU di Indonesia. Hasil kajian menunjukkan bahwa, berdasarkan delapan elemen dari lingkungan pengendalian yang ases, UIN Ar-Raniry mempunyai skor 62,79 (kategori cukup). Data ini menunjukkan bahwa walaupun termasuk ke dalam kategori cukup, masih banyak hal yang harus dilakukan oleh UIN Ar-Raniry sehingga dapat meminimalisir risiko pengelolaan universitas. Kondisi yang relatif sama juga ditemukan di PTKIN BLU lainnya seperti yang teridentifikasi selama proses wawancara dengan beberapa personil kuncinya. Sistem pengendalian internal yang diimplementasikan di UIN Ar-Raniry telah efektif dalam mengidentifikasi 69 sumber risiko yang berpotensi memberikan dampak negative bagi kinerja universitas, khususnya dalam hal keandalan laporan keuangan, keamanan aset, efektivitas and efisiensi kegiatan, dan kepatuhan terhadap aturan. Berdasarkan temuan kajian, PTKIN direkomendasikan untuk lebih focus terhadap kegiatan pengendalian internal dan menghubungkannya dengan asesmen risiko yang dievaluasi secara berkala.